A new Iolaus species (Lycaenidae: Theclinae) from the highlands of central Angola - Gardiner, Alan John (Zootaxa, 2025)
A new species of the tribe Iolaini, Iolaus francisi sp. nov., from the Highlands of central Angola is described, and available life history information is provided. The importance of conservation efforts in Angola is discussed and emphasized. An updated checklist of Iolaini of Angola is provided.